PERLINDUNGAN ANAK DI BAWAH UMUR TERHADAP PENYALAHGUNAAN NARKOBA DI KAWASAN PERBATASAN - Fernando, Yudha Febry (JURNAL AKTA YUDISIA, 2023)
AbstractChildren are the successors of the nation whose rights must be fulfilled, such asthe right to life and development. Childhood is a period that is very vulnerablewith various desires and hopes to achieve something or do something, includingnegative things which ultimately lead to the wrong path (for example usingdrugs). Especially in the border area (North Kalimantan), which can be said tobe the "entrance point" for the circulation of drugs supplied from abroad.Therefore, when there is a deviation in children becoming drug users, the stateneeds to pay attention to this problem. The rise of drug trafficking todaythreatens growth and development, such as the physical and mental health ofthe child. For this reason, the role of the state is needed to provide protectionfor children to avoid the influence of drugs. This study aims to find out (i) howto prevent drug abuse problems for minors in border areas; (ii) how is the legalprotection of minors in border areas who use drugs. The author uses a researchmethod with a normative legal approach, because he wants to research andstudy applicable legal products and regulate minors in border areas who usedrugs, namely through statutory regulations. To support the objectivity of theissues to be discussed, secondary data related to the issues is used, namelybooks and various other documents.Keywords: Protection, Children, Abuse, Drugs, Border Areas.